Landmark-based morphometric and meristic analysis in response to characterize the wild Bhagna, Labeo ariza populations for its conservation (Journal of the Bangladesh Agricultural University, 2018)
The landmark-based morphometric and meristic analysis of three different stocks from the Atrai, the Jamuna and the Kangsha of Bhagna (Labeo ariza, Hamilton 1807) were examined from a phenotypical point of view to evaluate the population structure and to assess shape variation. A total of 90 Bhagna (L. ariza) were collected from three different water bodies: the Atrai, the Jamuna and the Kangsha of Bangladesh during January, 2017. Ten morphometric and nine meristic characters were analyzed along with twenty-two truss network measurements. One way ANOVA showed that all morphometric, meristic and truss network measurement were significantly different (P